Civil liability of members of boards of a simple joint-stock company to a company - Węgliński, Konrad (Studia Iuridica Toruniensia, 2021)
On July 1, 2021, the catalog of commercial companies under Polish law was extended by a new type of company, i.e. a simple joint-stock company. It is assumed that a simple joint-stock company will constitute a modern form of a private capital company, intended in particular for innovative ventures and the so-called startups. The provisions governing a simple joint-stock company contain innovative solutions as compared to the existing companies operating under Polish law, including the possibility for shareholders to freely shape the internal organization of the company by choosing a monistic or dualistic system of company bodies, as well as regulating the civil liability of members of the governing bodies of a simple joint-stock company for damages caused to the company based on the business judgment rule. The aim of the article is to discuss the rules of civil liability of members of boards of a simple joint-stock company towards a company, with particular emphasis on the difference in terms of liability of officers of a limited liability company (Article 293 § 1 of the Code of Commercial Companies) and a joint-stock company (Article 483 § 1 of the Code of Commercial Companies). The article also attempts to assess the most important legislative novelty introduced into Polish law with the entry into force of the provisions concerning a simple joint-stock company, which is the implementation of the business judgement rule in Article 300(125) § 2 of the Commercial Companies Code.